Use of Satellite and In-Situ Data to Improve Sustainability - Kogan, Felix; Powell, Alfred; Fedorov, Oleg (NATO Science for Peace and Security Series C: Environmental Security, 2011)
More than 30-year operational satellite data have already been used for monitoring land, ocean and atmosphere. These applications have contributed to improve sustainable economy, produce healthy environment and enhance human life. The Advanced Research Workshop sponsored by NATO and organized by the USA's National Oceanic and Atmospheric Administration and Ukrainian's Space Agency bring the scientists with the most mature research designed for practical use. The goals were to select those which is used for services today and identify the areas to expand research and services. Scientific and application results of the Workshop presented in this book can be used today in agriculture, forestry, water resources, healthy coastal life and fisheries, climate and land cover change, anthropogenic activities and others. The presented papers provide information on how to use operational satellites and in situ measurements for early detection of large-scale droughts, floods and fires, diagnose crop and pasture annual losses, predict periods with health/unhealthy vegetation based on such climate forcing events as ENSO, monitor air quality and geomagnetic activities, assess land cover trends in responce to global warming etc. The available satellite/ground information and method is currently warn with a lead time sufficient to respond, recover and protect.